If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7x + -61 = 23 Reorder the terms: -61 + x + -7x = 23 Combine like terms: x + -7x = -6x -61 + -6x = 23 Solving -61 + -6x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '61' to each side of the equation. -61 + 61 + -6x = 23 + 61 Combine like terms: -61 + 61 = 0 0 + -6x = 23 + 61 -6x = 23 + 61 Combine like terms: 23 + 61 = 84 -6x = 84 Divide each side by '-6'. x = -14 Simplifying x = -14
| 7=2[r+6]-5 | | r(x)=x(13-0.04x) | | -15=10+5v | | -2x-10+3x=9 | | 62=-7v-1 | | 2[w+2]=10 | | 9x^4/3x^3 | | 3a-1/6-1-4a/12=1 | | 37=7+6x | | 40*x*52=31500 | | (40*x)+52=31500 | | 2n+25=5n+15 | | -x-7x-94=34 | | (40*x)*50=31500 | | -3(3p+6)-2(3-14p)=3(8+6p) | | 3(3-9y)= | | 7=7-7x | | 4m+10=-18 | | -75-5x-7x=81 | | 7/2a*5/a^2 | | x-31-4x=20 | | 8x+4=5x-10 | | 12.68+x+1.17=6.47 | | -(1-4m)-3m= | | -72-2x+8x=36 | | (2x-1)(x+3)=294 | | B=20a | | 2x+xy+3y=6 | | -55+8x-x=43 | | 3(x-2)+4=18 | | x/2-3x | | (40*x+3*1.5x)*52=31500 |